2010
DOI: 10.1590/s1415-790x2010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of patients with respiratory symptoms through active case finding and diagnosis of pulmonary tuberculosis among prisoners and related predictors in a jail in the city of Carapicuíba, Brazil

Abstract: Background Prisons offer a fertile setting for the transmission of tuberculosis due to the presence of many classic risk factors for both infection and disease: overcrowding, poor ventilation, and little sunlight. Prisoners are often malnourished and have poor hygiene and are more likely to have a background of alcohol and drug abuse. Objectives To determine the prevalence of prisoners with respiratory symptoms and pulmonary tuberculosis (PTB) through active case finding in a prisoner population of the count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 10 publications
0
13
1
13
Order By: Relevance
“…40 Addressing this challenge requires general health system strengthening, 5,6,43,44 including the prison sector and especially in LMICs. High-quality laboratory services with up-to-date biosafety measures, 19 updated and renewed detention centres 45 and TB prison hospitals, and continuous training programmes for both staff and prisoners should also be emphasized. 24,34,46 3.1.2.…”
Section: Results and Discussion: Current Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…40 Addressing this challenge requires general health system strengthening, 5,6,43,44 including the prison sector and especially in LMICs. High-quality laboratory services with up-to-date biosafety measures, 19 updated and renewed detention centres 45 and TB prison hospitals, and continuous training programmes for both staff and prisoners should also be emphasized. 24,34,46 3.1.2.…”
Section: Results and Discussion: Current Evidencementioning
confidence: 99%
“…59 IPT may effectively interrupt the progression of infection to active TB disease, but questions remain regarding whether IPT should be started in a facility with short imprisonment stays or in settings with high isoniazid resistance, and also which institution should take responsibility for the completion of IPT in the community once the prisoner is released. 19 Prison health services often have small budgets, 45,60,61 which, in addition to the lack of skilled and motivated manpower, 19,22,38 may jeopardize successful TB control programmes in prisons. Public health attention from donors and other stakeholders towards populations at risk of TB has increased in recent years following the emergence of HIV/AIDS, the more stringent application of human rights principles, health inequalities, and health governance.…”
Section: Preventive Treatment Of Persons At High Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we found that primary MDR-TB cases were significantly more likely to be living with fewer than two persons at the time of diagnosis. [18][19][20] Further investigation is needed to understand the role played by population density and household crowding in the spread of primary MDR-TB in SJL. Social mixing outside of households, such as in bars, cafes, schools and workplaces, has an important role in TB transmission.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of TB in prison populations are likely to be attributable to the fact that a disproportionate number of prisoners are from population groups already at high risk of TB infection and TB disease .Furthermore, the prison setting, where segregation criteria are based on crime characteristics rather than on public health concerns, may facilitate transmission. In addition, late case detection, inadequate treatment of infectious cases, high turnover of prisoners, and poor implementation of TB infection control measures are all known factors contributing to transmission of Mycobacterium tuberculosis [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%